2022
DOI: 10.1186/s12974-022-02518-7
|View full text |Cite
|
Sign up to set email alerts
|

Apelin alleviated neuroinflammation and promoted endogenous neural stem cell proliferation and differentiation after spinal cord injury in rats

Abstract: Background Spinal cord injury (SCI) causes devastating neurological damage, including secondary injuries dominated by neuroinflammation. The role of Apelin, an endogenous ligand that binds the G protein-coupled receptor angiotensin-like receptor 1, in SCI remains unclear. Thus, our aim was to investigate the effects of Apelin in inflammatory responses and activation of endogenous neural stem cells (NSCs) after SCI. Methods Apelin expression was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Notably, in recent studies, apelin/APJ complex expression in oligodendrocytes correlated with age-associated changes in remyelination efficiency through the translocation of myelin regulatory factors ( 154 ). Apelin promotes the differentiation of neural stem cells ( 155 ) and can therefore represent not only an anti-inflammatory factor but also contribute to repair processes observed during the course of MS.…”
Section: Anti-inflammatory Adipokinesmentioning
confidence: 99%
“…Notably, in recent studies, apelin/APJ complex expression in oligodendrocytes correlated with age-associated changes in remyelination efficiency through the translocation of myelin regulatory factors ( 154 ). Apelin promotes the differentiation of neural stem cells ( 155 ) and can therefore represent not only an anti-inflammatory factor but also contribute to repair processes observed during the course of MS.…”
Section: Anti-inflammatory Adipokinesmentioning
confidence: 99%
“…The results of GO biological processes and KEGG pathways of hub genes were in line with many previous studies. Inflammation, oxidative stress, IL-17 signaling pathway, and so on were regarded as indispensable parts of specific mechanisms in SCI [43][44][45]. There are 93 molecules involved in IL-17 family signaling events in the IL-17 signaling pathway resource [46].…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] Another report stated that Apelin contributes proliferation and neural differentiation of neural stem cell. [ 49 ] Moreover, knock down of Aplnr led to the decreased cardiomyocyte differentiation from hESC and had a detrimental effect on the contractility in 3D engineered heart tissues. [ 50 ] In addition to these data, protein profiling and mRNA analysis indicated that various signaling pathways, including EGFR, TGF‐beta, Wnt, PDGF, and FGF signaling pathways, were affected by Aplnr signaling during MSC differentiation.…”
Section: Discussionmentioning
confidence: 99%